Political Attitudes and Perceptions of Batswana: The Implications for Sustainable Economic and Human Development in Sub-Saharan Africa (London Journal of Research In Humanities and Social Sciences, 2023)
Botswana stands out among sub-Saharan African nations for its economic and human  development. The central aim of this paper is to consider what makes Botswana different. This  paper asserts that the attitudes and perceptions of Batswana (i.e., the people of Botswana)  contribute to the nation’s economic and human development. It considers how Batswana’s  attitudes and perceptions differ from populations in other sub-Saharan African countries and the implications of such differences in explaining what makes Botswana’s economic and human  development patterns stand out from other sub-Saharan African nations. This paper’s findings  indicate that political attitudes and perceptions of the people in sub-Saharan Africa, such as  Botswana, are essential and should not be ignored as factors influencing economic and human  development success. Furthermore, it suggests there may be something different about how  democracy and governance operate in Botswana that shapes attitudes and perceptions relative to  other sub-Saharan African nations.
Keywords: Political Marketing; Election Decisions; COVID-19; Indigenous Knowledge; Infection diseases; coloniality